RESPONS PERTUMBUHAN RUMPUT Brachiaria humidicola cv Tully DENGAN PEMBERIAN PUPUK ORGANIK BOKASHI KOTORAN AYAM PETELUR - Korejang, Merlin; Anis, Selvie D.; Kaunang, W.B.; Sumolang, C.I.J. (Universitas Sam Ratulangi, 2019)
GROWTH RESPONSE OF Brachiaria humidicola cv Tully grass WITH ORGANIC FERTILIZER BOKASHI LAYING CHICKEN. This study aims to determine the growth response i.e stolon length, number of nodes, number of phytomers, and number of tillers of Brachiaria humidicola cv Tully with bokashi organic laying hens fertilizer. The completely randomized design was applied using four treatments and five replications for each treatment. The treatments were assigned level of bokashi. The levels of bokashi that B0 = 0 tons/ha (control), B1 = 2 tons/ha (1.8 kg/plot), B2 = 4 tons/ha (3.6 kg/plot) and B3 = 6 tons/ha (5.4 kg/plot). The variables measured consisted of stolon length, number of nodes, number of phyitomers, number of tillers. The Results of analysis of variance showed that treatment very significantly different (P <0.01) on stolon length, number of phyitomers, number of tillers and significantly different (P <0.05) on the number of nodes. Test of Honest Significance Difference (HSD) showed that B1 (1.8 kg / plot), B2 (3.6 kg / plot), and B3 (5.4 kg / plot) have higher length of stolone, number of phyitomers and number of tillers than B0. B3 and B2 had higher numbers of nodes than B0. It was concluded that the level 1.8 kg/plot organic fertilizer bokashi chicken laying equivalent to 2 tons/ha gave highest B. humidicola cv Tully growth response. Keywords: growth, B. humidicola cv Tully, bokashi laying Chicken